Treatment-Refractory Central Centrifugal Cicatricial Alopecia Responsive to a Novel Botanical Treatment - Umar S; Kan P; Carter MJ; Shitabata P (Dove Medical Press, 2022)
Sanusi Umar,1- 3 Petrina Kan,4 Marissa J Carter,5 Paul Shitabata1,2,6 1Department of Medicine, University of California at Los Angeles, Los Angeles, CA, USA; 2Division of Dermatology, Department of Medicine, Harbor-UCLA Medical Center, Torrance, CA, USA; 3Dr. U Hair and Skin Clinic, Manhattan Beach, CA, USA; 4Department of Molecular Biology, University of California at Los Angeles, Los Angeles, CA, USA; 5Strategic Solutions, Inc, Bozeman, MT, USA; 6Dermatopathology Institute, Torrance, CA, USACorrespondence: Sanusi Umar, Dr. U Hair and Skin Clinic, 2121 N. Sepulveda Avenue, Suite 200, Manhattan Beach, CA, 90266, USA, Tel +1 (310) 318-1500, Fax +1 (310) 318-1590, Email drumar@dru.comPurpose: Central centrifugal cicatricial alopecia (CCCA) is the most common cause of scarring alopecia in women of African descent. However, current treatments for CCCA, such as immunosuppressants and immunomodulatory pharmaceutical agents, have suboptimal efficacy and undesirable side effects. This case series reports the therapeutic effect of a new botanical formulation (Dr. UGro Gashee) in four patients with histologically supported diagnoses of CCCA. The formulations contain at least three phytoactive ingredients that affect multiple targets in the cascade of pathophysiologic events contributing to CCCA. Possible mechanisms of action include anti-inflammatory effects, inhibiting proinflammatory cytokines, and the net antifibrotic effect of inhibiting transforming growth factor-beta while upregulating AMP-activated protein kinase and peroxisome proliferator-associated receptor-gamma activity.Patients and Methods: Four African American women with treatment-refractory CCCA were treated with a new topical botanical formula (cosmeceutical) alone or in combination with its oral formulation (nutraceutical) for 8 weeks to 1 year. The cosmeceutical and nutraceutical treatments contain similar phytoactive ingredient profiles. Treatment outcomes were collected using documented patient reports and images and by direct observation.Results: In all patients, scalp pruritus cessation occurred within 2 weeks of treatment, and significant hair regrowth was observed within 2 months. All patients reported a high satisfaction level without adverse effects.Conclusion: Patients with treatment-refractory CCCA responded to the novel botanical treatment reported in this study. Further evaluations in a controlled trial with more patients are warranted.Keywords: scarring alopecia, follicular degeneration syndrome, hot comb alopecia, African American women, hair loss, cosmeceutical, nutraceutical, phytoactive